Pengaruh Green Accounting, Material Flow Cost Accounting, dan Environmental Performance terhadap Sustainable Development - Irene Kurnianingtyas; Luh Putu Puji Trisnawati (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This study aims to analyze the impact of green accounting, material flow cost accounting (production cost, area size, production output), and environmental performance on sustainable development. The population of this study includes energy sector companies in the subsectors of oil, gas, coal, and palm oil listed on the Indonesia Stock Exchange (IDX) during 2020-2022. Data were collected secondary through purposive sampling, resulting in 23 companies with 69 observations, based on certain criteria. The analysis methods include descriptive statistics, classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity), multiple regression, coefficient of determination, and hypothesis tests t and F using Eviews. The results show that green accounting, production costs, and production output have an impact on sustainable development, while area size and environmental performance do not have an impact. This study is limited by the availability of data and the number of sample companies, as well as the subjective measurement of green accounting. It is recommended to expand the sample, use more objective measurements, and add variables such as green intellectual capital, environmental cost, and internal corporate governance strength for future research.